Selection and Recruitment in the Healthcare Professions Research, Theory and Practice (Springer International Publishing, 2018)
How we recruit future healthcare professionals is critically important, as the demand for high quality healthcare increases across the globe. This book questions what the evidence tells us about how best to select those most suited to a career in healthcare, ensuring that the approaches used are relevant and fair to all who apply. The editors of this collection take a comprehensive look at the latest research surrounding recruitment and selection into healthcare roles. Each chapter is authored by leading experts and, using international case material, the practical implications for workforce policy are explored. They review the key stages in designing effective selection systems and discuss how best to evaluate the quality of selection processes. Evidence from role analysis studies as well as the effectiveness of different selection methods including aptitude and situational judgment tests, personality assessment and interviews are examined. Chapters also cover approaches to student selection and recruitment for postgraduate trainees through to senior appointments. Finally they highlight contemporary issues in recruitment, including the use of technology, selecting for values, candidate perceptions, coaching issues and how best to promote diversity and widening access.